Rethinking Cloud-hosted Financial Exchanges for Response Time Fairness - Goyal, Prateesh; Marinos, Ilias; Gupta, Eashan; Bandi, Chaitanya; Ross, Alan; Chandra, Ranveer (ACM HotNets, 2022)
In this paper, we consider the problem of supporting modern financial exchange services on the cloud premises. Important exchange services rely on predictable, equal latency from the servers to the participants for fair competition. Existing cloud networks, however, are unable to offer such property, as they were not originally designed for this purpose. We attempt to tackle the problem of unfairness that stems from the lack of determinism in cloud networks. We argue that predictable or bounded latency is not necessary to achieve fairness. Inspired by the use of logical clocks in distributed systems, we propose a new approach that instead corrects for differences in latency to the participants for fairness. We evaluate our approach in simulation and show that it is feasible to achieve fairness under highly variable network latency. Our approach is deployable in contemporary cloud environments; it avoids limitations of state-of-the-art and outperforms it.